Seated Pulmonary Artery Pressure Monitoring in Patients With Heart Failure - Jason L. Guichard; Eric L. Bonno; Michael E. Nassif; Taiyeb Khumri; David Miranda; Orvar Jonsson; Hirak Shah; Tamás Alexy; Gregory Macaluso; James P. Sur; Gavin W. Hickey; Patrick J. McCann; et al. (2024)
Monitoring supine pulmonary artery pressures to guide heart failure (HF) management has reduced HF hospitalizations in select patients. The purpose of this study was to evaluate the effect of managing seated mean pulmonary artery pressure (mPAP) with the Cordella Pulmonary Artery sensor on outcomes in patients with HF. Following GUIDE-HF (Hemodynamic-GUIDEd Management of Heart Failure Trial), with U.S. Food and Drug Administration input, PROACTIVE-HF (A Prospective, Multi-Center, Open Label, Single Arm Clinical Trial Evaluating the Safety and Efficacy of the Cordella Pulmonary Artery Sensor System in NYHA Class III Heart Failure Patients trial) was changed from a randomized to a single-arm, open label trial, conducted at 75 centers in the USA and Europe. Eligible patients had chronic HF with NYHA functional class III symptoms, irrespective of the ejection fraction, and recent HF hospitalization and/or elevated natriuretic peptides. The primary effectiveness endpoint at 6 months required the HF hospitalization or all-cause mortality rate to be lower than a performance goal of 0.43 events/patient, established from previous hemodynamic monitoring trials. Primary safety endpoints at 6 months were freedom from device- or system-related complications or pressure sensor failure. Between February 7, 2020, and March 31, 2023, 456 patients were successfully implanted in modified intent-to-treat cohort. The 6-month event rate was 0.15 (95% CI: 0.12-0.20) which was significantly lower than performance goal (0.15 vs 0.43; P < 0.0001). Freedom from device- or system-related complications was 99.2% and freedom from sensor failure was 99.8% through 6 months. Remote management of seated mPAP is safe and results in a low rate of HF hospitalizations and mortality. These results support the use of seated mPAP monitoring and extend the growing body of evidence that pulmonary artery pressure–guided management improves outcomes in heart failure. (Multi-Center, Open Label, Single Arm Clinical Trial Evaluating the Safety and Efficacy of the Cordella Pulmonary Artery Sensor System in NYHA Class III Heart Failure Patients trial [PROACTIVE-HF]; NCT04089059)